Got technology? The impact of computers and cell phones on productivity in a difficult business climate ; evidence from firms with female owners in Kenya - Nidhiya Menon (Institute for the Study of Labor (IZA), 2011)
Firms in Kenya rely on technologies such as computers, cell-phones, and generators to overcome constraints associated with regulations, infrastructure, security, workforce, corruption, and finance. This study shows that such reliance has significant positive impacts on productivity as measured by value-added per worker, especially for firms with female principal owners. The exogenous component of technology ownership is isolated by using information on the regional presence of missionary schools from Kenya's colonial past, as well as geographical indicators such as rainfall, changes in forest cover, and average regional elevation. Results indicate that for firms with female owners, technology adoption improves value-added per worker by about 49 percentage points. It is also statistically evident that for such firms, the ownership of technologies such as computers, cell-phones, and generators succeeds in mitigating the costs of business obstacles. For male-owned firms, such patterns are absent.
urn:nbn:de:101:1-201104084293
Keywords: O14; O33; L22; N37; 330; technology; computers; cell-phones; business obstacles; Kenya; firms; female owners; Technologiewahl; Weibliche Führungskräfte; Computergestütztes Verfahren; Mobilkommunikation; Arbeitsproduktivität; Unternehmensentwicklung; Kenia